High diversity and multiple invasions to North America by fungi grown by the northern-most Trachymyrmex and Mycetomoellerius ant species. (April 2020) - Luiso, Joseph; Kellner, Katrin; Matthews, Alix E.; Mueller, Ulrich G.; Seal, Jon N.
Abstract: Lower diversity at range margins of expanding populations is thought to reduce host-symbiont specificity of obligate symbioses. Selection for relaxed symbiont recognition systems is thought to occur when most, if not all, symbionts available to a host are genetically similar. This study evaluated whether the genetic diversity of symbiont populations along a range margin (North America) were lower than those of Neotropical populations in fungus gardening ants (subtribe Attina). Using phylogenetic, population-genetic and community-ecology approaches, we tested the hypotheses that North American fungal populations are genetically less diverse than Neotropical populations and whether they exhibit evidence of recent population expansion. Results indicated that fungal diversity is somewhat greater in the Neotropics than North America; however, North American populations are very diverse because all lineages found in the Neotropics are also represented in North America. Moreover, we found evidence of recent population expansion in both the Neotropics and North America.